Gallbladder Removal Simulation for Laparoscopic Surgery Training: A Hybrid Modeling Method - Kim, Youngjun; Chang, Dongjune; Kim, Jungsik; Park, Sehyung (SCIENCE PRESS, 2013)
Laparoscopic surgery has many advantages, but it is difficult for a surgeon to achieve the necessary surgical skills. Recently, virtual training simulations have been gaining interest because they can provide a safe and efficient learning environment for medical students and novice surgeons. In this paper, we present a hybrid modeling method for simulating gallbladder removal that uses both the boundary element method (BEM) and the finite element method (FEM). Each modeling method is applied according to the deformable properties of human organs: BEM for the liver and FEM for the gallbladder. Connective tissues between the liver and the gallbladder are also included in the surgical simulation. Deformations in the liver and the gallbladder models are transferred via connective tissue springs using a mass-spring method. Special effects and techniques are developed to achieve realistic simulations, and the software is integrated into a custom-designed haptic interface device. Various computer graphical techniques are also applied in the virtual gallbladder removal laparoscopic surgery training. The detailed techniques and the results of the simulations are described in this paper.
Keywords: MECHANICAL-BEHAVIOR; HAPTIC INTERACTION; DEFORMABLE MODELS